2009
DOI: 10.1177/0267323108101831
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomy of Media Hypes

Abstract: ■Media hypes are a well known phenomenon. They occur on a regular basis and attract much media attention, but there is very little knowledge about them. This article supplements Vasterman's analysis of the phenomenon and presents new empirical evidence. Through a case study of five Danish media hypes occurring between 2000 and 2005, the article shows that not every event has the potential to trigger a media hype: it must, of course, satisfy the general news values, but should also contain some violation of nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 10 publications
0
33
1
Order By: Relevance
“…Brossard et al, 2004;Downs, 1972;McComas & Shanahan, 1999;Nisbet & Huge, 2006;Shih et al, 2008). The specifics of short event-based issueattention cycles have only been investigated for events that trigger an extremely high level of attention, such as media hype or media storms (Boydstun, Hardy, & Walgrave, 2014;Wien & Elmelund-Praestekaer, 2009). Furthermore, so far, most studies examine the process only in the traditional mass media.…”
Section: Research On the Dynamics Of Sub-topics And Interpretationsmentioning
confidence: 99%
“…Brossard et al, 2004;Downs, 1972;McComas & Shanahan, 1999;Nisbet & Huge, 2006;Shih et al, 2008). The specifics of short event-based issueattention cycles have only been investigated for events that trigger an extremely high level of attention, such as media hype or media storms (Boydstun, Hardy, & Walgrave, 2014;Wien & Elmelund-Praestekaer, 2009). Furthermore, so far, most studies examine the process only in the traditional mass media.…”
Section: Research On the Dynamics Of Sub-topics And Interpretationsmentioning
confidence: 99%
“…This positive feedback loop models the reverse influence of the mass media on sponsors as shown by policy agenda-setting studies (Walgrave & van Aelst, 2006;Yanovitzky, 2002). Journalists may interview sponsors as experts for a topic (Wien & Elmelund-Praestekaer, 2009). Even if sponsors initially refuse statements, massive public attention might press them to react (Mahon & Waddock, 1992).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Figure 1 shows the stylized pattern of the issue-attention cycle, as observed in many empirical studies (see Kolb, 2005, p. 95, for a similar illustration). During the whole lifespan of an issue, this pattern may repeat itself several times (Wien & Elmelund-Praestekaer, 2009) and also create superordinate patterns of meta-cycles (Djerf-Pierre, 2013). Throughout the article, the term issue-attention cycle is used only to denote this specific pattern of media attention, while news wave generally stands for "a sharp and continuous increase of reporting on a specific issue for a limited period of time" (Geiß, 2011, p. 272).…”
mentioning
confidence: 99%
“…Vasterman [14] characterizes media hypes as being selfreinforcing, potentially being driven less by external events after the triggering event and more by discussion about itself [14], [15] until the issue is crowded out by another topic. Vasterman suggests a smooth left-skewed distribution as a model, while Wein and Elmelund-Praestekaer [15] find evidence of a decreasing oscillatory pattern.…”
Section: A Firestormsmentioning
confidence: 99%
“…Vasterman [14] characterizes media hypes as being selfreinforcing, potentially being driven less by external events after the triggering event and more by discussion about itself [14], [15] until the issue is crowded out by another topic. Vasterman suggests a smooth left-skewed distribution as a model, while Wein and Elmelund-Praestekaer [15] find evidence of a decreasing oscillatory pattern. For news cycles, Leskovec et al [16] found a 'saw-toothed' shaped increase followed by an exponential decay, which they were able to reproduce in a simulation model that combined an imitation effect and a recency effect.…”
Section: A Firestormsmentioning
confidence: 99%